2017
DOI: 10.3390/v9070187
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Human Papillomavirus Induced Skin Carcinogenesis

Abstract: Infection of the cutaneous skin with human papillomaviruses (HPV) of genus betapapillomavirus (βHPV) is associated with the development of premalignant actinic keratoses and squamous cell carcinoma. Due to the higher viral loads of βHPVs in actinic keratoses than in cancerous lesions, it is currently discussed that these viruses play a carcinogenic role in cancer initiation. In vitro assays performed to characterize the cell transforming activities of high-risk HPV types of genus alphapapillomavirus have marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 72 publications
(83 reference statements)
2
49
0
5
Order By: Relevance
“…While normal epithelial cells exit the cell cycle upon differentiation or UV-induced DNA damage, HPV-infected cells are able to circumvent the governing checkpoint mechanisms and force cells to remain in the cell cycle, allowing for synthesis of cellular proteins necessary for viral genome amplification. 8,9 The betaHPV DNA loads in actinic keratoses exceed those in SCC, which suggests a particular involvement of betaHPV in the early stages of cutaneous oncogenesis. 4,5 The oncogenic potential of HPV of the genus betapapillomavirus (betaHPV) in skin carcinogenesis was originally identified in patients suffering from the rare inherited disease epidermodysplasia verruciformis (EV), who have an increased susceptibility to betaHPV infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While normal epithelial cells exit the cell cycle upon differentiation or UV-induced DNA damage, HPV-infected cells are able to circumvent the governing checkpoint mechanisms and force cells to remain in the cell cycle, allowing for synthesis of cellular proteins necessary for viral genome amplification. 8,9 The betaHPV DNA loads in actinic keratoses exceed those in SCC, which suggests a particular involvement of betaHPV in the early stages of cutaneous oncogenesis. 4,5 The oncogenic potential of HPV of the genus betapapillomavirus (betaHPV) in skin carcinogenesis was originally identified in patients suffering from the rare inherited disease epidermodysplasia verruciformis (EV), who have an increased susceptibility to betaHPV infections.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, immunosuppressed organ-transplant-recipients also have a higher susceptibility to betaHPV infections of the skin as well as an increased risk of developing SCC compared to healthy individuals. 8,9 The betaHPV DNA loads in actinic keratoses exceed those in SCC, which suggests a particular involvement of betaHPV in the early stages of cutaneous oncogenesis. 10 To unravel the molecular mechanisms underlying HPV8mediated skin tumor development, we previously expressed the complete early genome region (CER, inducing simultaneous expression of E6, E7, E1, E1^E4, E2) in primary human adult keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of integrin network are linked to skin carcinogenesis. Accordingly, studies in monolayer and organotypic cultures showed that beta HPV8 is able to alter the integrin network, promoting invasion of human keratinocytes into the dermis (77)(78)(79).…”
mentioning
confidence: 99%
“…Cutaneous HPV types of different genera are common on healthy skin (Antonsson et al, 2000). However, they are also found in several skin lesions such as benign skin warts (de Villiers et al, 2004; International Agency on Research on Cancer (IARC), 2012), and some types have been discussed to be involved in skin carcinogenesis (Hufbauer and Akgül, 2017).…”
Section: Introductionmentioning
confidence: 99%